Model Konseptual Mutu Pendidikan Lembaga Pesantren Melalui Integrasi Nilai Ihsan dan Itqan - Elok Nadiatun Naimah; Muhammad Khalivi Abqary Mubaroki; Helmi Syaifuddin (JURNAL RISET MANAJEMEN (JURMA), 2026)
This study aims to formulate a framework for the quality of pesantren education through the integration of ihsan and itqan values into the quality assurance system. This study is based on the issue of the limitations of modern education governance that tends to be fixated on the fulfillment of formal-material aspects, but less touching the ethical foundation and spiritual motivation that is the root of Islamic educational institutions. Through a conceptual approach, this article analyzes the alignment of Islamic values in the educational structure in order to build a quality model based on religious principles. The results showed that the quality governance of pesantren was built by placing ihsan as the root of an organizational culture that prioritizes transcendental responsibility, while the itqan principle ensures that the implementation of every educational activity takes place in a systematic, disciplined, and has high quality standards. The combination of these two values results in an independent internal oversight mechanism. These findings provide a contribution to the development of Islamic education governance that unites religious commitment with professional demands. In practical terms, this model is a reference for pesantren managers in strengthening institutional accountability without compromising the identity of the pesantren.